Drugs in fall versus non-fall accidents with major trauma – A population-based clinical and medico-legal autopsy study. (March 2019) - Acosta, S.; Andersson, L.; Bagher, A.; Wingren, C.J.
Highlights: Population-based studies on major trauma need clinical and medico-legal data. The autopsy rate for fall accidents was lower than for non-fall accidents. The drug rate at autopsy was 77% in falls, twice the rate of non-fall accidents. Presence of sedatives at autopsy were found more often in falls vs non-falls. Guidelines at hospital managing polypharmacy may prevent fall recidivism. Abstract: Background: The main aim of the present population-based study was to compare drugs in fall versus non-fall accidents causing major trauma, including both clinical and medico-legal autopsy data. Methods: All individuals with accidents resulting in major trauma, a new injury severity score (NISS) > 15 or lethal outcome was identified at hospital and/or the Department of Forensic Medicine between 2011 and 2013. Modified Downton Fall Risk Index ranged from 0 to 7, and was based on specific pharmaceuticals (max 5 points), previous fall (1 point) and cognitive impairment (1 point). Results: One hundred and four individuals with major traumatic accidents were identified, 38 (36.5%) died. The median modified Downton Fall Risk Index was 2 for fall accidents and 0 for non-fall accidents (p < 0.001). Modified Downton Fall Risk Index was an age-independent factor associated with fall accident (p < 0.001). The medico-legal autopsy rate for in-hospital patients was 50% (6/12) for fatal fall accidents in comparison with 92.3% (12/13) for fatal non-fall accidents (p = 0.03). In individuals undergoing medico-legal autopsy, the proportion of individuals with any detected drug was 77% in fall accidents compared to 39% in non-fall accidents (p = 0.036). The presence of sedatives (p = 0.002) and bensodiazepines (p = 0.023) were higher for fall accidents compared to non-fall accidents. Conclusion: This population-based study on accidents with major trauma showed that drugs had high impact on fall accidents with major trauma. It seems warranted from a public health perspective to study if implementation of medication review guidelines at hospital managing polypharmacy issues may prevent fall accident recidivism.